Mesenchymal Stem Cells Reduce Inflammation in a Mouse Model of Lyme Arthritis - Weijiang Ma; Jing Kong; Mengqin Zhang; Hanxin Wu; Shanshan Wan; Xin Liu; Bingxue Li; Yan Dong; Lei Zhong; Weijie Ma; Li Gao; Xinya Wu; et al. (Stem Cells International)
Lyme disease (LD), a zoonotic infectious disease caused by Borrelia burgdorferi (B. burgdorferi), can affect various organs, including the skin, heart, nervous system, and joints. Lyme arthritis (LA) is the most common and severe late-stage presentation of LD, often presenting with intermittent joint swelling and pain. Although antibiotics are effective in most patients with LA, some patients may continue to experience arthritis symptoms for months or years after standard treatment, which poses a serious threat to their quality of life. Therefore, more effective treatments are urgently needed. The purpose of this study was to evaluate the therapeutic effects of human umbilical cord mesenchymal stem cells (hUC-MSCs) on LD in Kunming (KM) mice. A bilateral hind limb LA model was established by infecting KM mice with B. burgdorferi. Low and high doses of hUC-MSCs (1 × 106 and 2 × 106 cells, respectively) were injected (one time every 2 days) into the right tibiotalar joints of the mice, whereas the left tibiotalar joints were pricked without injecting cells (sham operation). The therapeutic effects of the hUC-MSCs were evaluated through morphological examination, measurement of hind limb diameter, imaging assessment (X-ray), and measurement of inflammatory factor levels. Spirochete burden was assessed by quantitative real-time polymerase chain reaction (qPCR). Morphological, hind limb diameter, and imaging analyses showed that the low and high hUC-MSC doses significantly reduced bilateral hind limb swelling in the LA mice. Histological (hematoxylin and eosin staining) examination of tibiotalar joint sections showed that when compared with the control group, inflammatory cell infiltration, and bilateral hind limb tissue damage were reduced in the two treatment groups. Enzyme-linked immunosorbent assays revealed that the levels of IL-6 and TNF-α in lysates from the bilateral tibiotarsal joints were significantly lower in the two treatment groups than in the control group. QPCR results showed that hUC-MSCs treatment had no significant effect on the spirochete load in the tibiotarsal joint. Our findings indicate that hUC-MSCs can alleviate inflammation in the KM mouse model of LA without increasing B. burgdorferi burden., which is expected to be a new potential method for the treatment of LA.